Implementation of Science Learning Alternative School Sanggar Anak Alam (SALAM) Nitiprayan Bantul Yogyakarta - Dawim, Mardianto; Priyono Budi P., Andreas; W.H, Nugrahaningsih (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
This case study aims to analyze the material, process and evaluation of Science learning in SALAM Yogyakarta. This research is a qualitative research. The data was collected by participatory observation, in-depth interviews and documentation. Testing the validity of the data using the degree of confidence criteria with triangulation techniques. The results showed that the implementation of Science learning in SALAM Yogyakarta did not have special subjects teaching Science material. Science material does not stand up as a formal school subject manifested in Natural Science. The method used in the learning process is research and learning cycles. Learning resources are adapted to the research theme taken by each child. Evaluations are conducted periodically and at any time based on the processes and attitudes that appear during conducting research.